2018
DOI: 10.2337/db18-1625-p
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Diabetes Mellitus among Undocumented Immigrants in an Indigent Care Program in Riverside, California

Abstract: Background: Acculturated undocumented immigrants (UI) in the U.S. with sedentary lifestyle and poor eating habits are at risk for diabetes mellitus (DM). UI also face adverse social, economic, and psychological stressors that may lead to poor clinical outcomes. No study to date has assessed DM prevalence and clinical outcomes among UI. Methods: Riverside University Health System, a county health system, provides medical care for indigent patients including UI. Of 8,466 UI receiving indigent care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Undocumented Latinos were the only immigrant group that had lower odds of current smoking and binge drinking compared with US-born Latinos. This is consistent with the findings of a claims-based study in Southern California that found low rates of smoking and drinking among undocumented immigrants in a county health system [31]. While we did not find differences in leisure walking, it should be noted that this measure does not account for other forms of physical activity such as work-related physical activity (e.g., farming, construction) or transportation.…”
Section: Discussionsupporting
confidence: 91%
“…Undocumented Latinos were the only immigrant group that had lower odds of current smoking and binge drinking compared with US-born Latinos. This is consistent with the findings of a claims-based study in Southern California that found low rates of smoking and drinking among undocumented immigrants in a county health system [31]. While we did not find differences in leisure walking, it should be noted that this measure does not account for other forms of physical activity such as work-related physical activity (e.g., farming, construction) or transportation.…”
Section: Discussionsupporting
confidence: 91%
“…Latinos are also more likely to reside in high-density and multigenerational housing—hampering social distancing, increasing the exposure of the elderly to COVID-19, generating mental stressors (Bibbins-Domingo, 2020; Rodriguez-Diaz et al, 2020), and challenging the “implicit presumption of a safe place in shelter-in-place and social distancing directives” (Cholera et al, 2020: 1). At the community level, low-income areas are less likely to have adequate COVID-19 testing and care (Rodriguez-Diaz et al, 2020) and the higher prevalence of uncontrolled chronic diseases, such as diabetes, make Latinos more susceptible to severe forms of COVID-19 (Lee et al, 2018).…”
Section: Research Frameworkmentioning
confidence: 99%
“…Latinos are also more likely to reside in high density and multi-generational housing -hampering social distancing, increasing the exposure of the elderly to COVID-19, generating mental stressors (Bibbins-Domingo, 2020;Rodriguez-Diaz et al, 2020), and challenging the "implicit presumption of a safe place in shelterin-place and social distancing directives" (Cholera et al, 2020: 1). At the community level, lowincome areas are less likely to have adequate COVID-19 testing and care (Rodriguez-Diaz et al, 2020) and the higher prevalence of uncontrolled chronic diseases, such as diabetes, make Latinos more susceptible to severe forms of COVID-19 (Lee et al, 2018).…”
Section: Intersectional Vulnerabilities Of Undocumented Latino Immigrants During Covid-19mentioning
confidence: 99%